PELESTARIAN KULINER TRADISIONAL JENANG SURO DENGAN PROMOSI MELALUI MEDIA SOSIAL - Haq, Rizkarina Zahrul; Fauzi , Ria Riski; Choirunnisa , Laili; Hasanah , Febby Nur; Ainiyah , Fifrida Silvia Qurrotul; Farizy , Moh. Zidan Al; Iksan, Iksan (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Glagah Village has a unique culture and is carried out every year in the month of Suroh, namely a village clean activity called Gelar Songo. One of the series in the Songo Title event is Jenang Suro. Jenang Suro with a distinctive white color with ingredients such as sticky rice, coconut, coconut milk, brown sugar, pandan leaves filled with nuts, shredded chicken and sliced eggs. Students have an important role in preserving and introducing the Jenang Suro tradition in Glagah Village, one of which is through social media such as uploading videos and photos on Instagram. This research aims to see the participation of KKN 127 students in the Songo Title series, namely Jenang Suro, in introducing and preserving traditional events in Glagah Village. The research methods used were interviews, observation and documentation. The participation of KKN 127 students in preserving culinary culture through social media is very effective in increasing awareness and appreciation of traditional culinary. competitive market.